Harposporium incensis sp. nov. a South American cordycipitoid species exhibiting inter-phylum host-jumping and having potential as a biological control agent for pest management - Ming-Jun Chen; López-Juan Chavez; Jin-Yuan Kang; Jiang-Xin Hu; Jian-Fei Dong; You-Jiu Tan; Zhu-An Chen; Bo Huang; Chun-Ru Li; Chang-Sheng Sun; Nigel Hywel-Jones; Xing-Zhong Liu; et al. (Mycology)
Macro- and microscopic morphological studies and multilocus phylogenetic analysis were made on larval specimens of a ghost moth collected from a pigeon pea plantation in Huánuco, Peru. DNA sequences from the cadaver and the fungal isolates obtained represented a monophyletic clade based on the phylogeny. All morphological characters and molecular data showed that the pathogenic fungus infecting the ghost moth larvae was an unknown cordycipitoid species, herein described as, Harposporium incensis sp. nov. based on morphological features and multilocus phylogenetic analysis on the cadaver and fungus isolated from the same specimen. The far-related and ecologically different hosts of teleomorph and anamorph of this new species display a peculiar inter-phylum host jumping between the insect Trichophassus giganteus of the phylum Arthropoda and the nematode Caenorhabditis elegans of the phylum Nematoda and have biological control potential.